ODRA2D – two-dimensional cascade flood modelling for the Odra River – development and applications - Robert Jerzy Banasiak (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Development of new hydrodynamic numerical tools for simulations of the flow in the Odra River valley for the flood hazard assessment and management